Special Topics in Resuscitation - Aslanidis, Theodoros K. (IntechOpen, 2018)
This book, published by "IntechOpen," highlights some interesting topics of resuscitation. Divided into two sections, the book emphasizes details about the role of the Emergency Medical Services Physician in prehospital resuscitation as well as special circumstances, such as resuscitation in the delivery room and possible future applications in the field, like the use of transthoracic impedance signal. The authors offer the reader not only a "vigorous" review of the current literature but also a research path for further advancement.